SISTEM KONTROL KUALITAS UDARA DALAM RUANGAN BERBASIS ARDUINO - Derik Dwi Heavyanto; Yudi Kristyawan; Budi Santoso (SKANIKA: Sistem Komputer dan Teknik Informatika, 2026)
Indoor air quality issues are increasing due to high exposure to pollutants such as carbon monoxide (CO) and PM2.5 particulates, especially in buildings located near highways. Most air control devices are still operated manually or continuously without considering actual conditions, making them inefficient and unresponsive to changes in air quality. This study designed an Arduino-based air quality control system capable of real-time monitoring and automatic control using MQ-7, PMS5003, and PIR sensors. The method employed was a prototype approach that included hardware design, microcontroller programming, and system function testing using black-box testing. The testing scenarios included conditions where CO and PM2.5 levels exceeded thresholds, human presence detection, and a combination of all parameters in two test rooms. The test results showed that the system was able to respond well to all scenarios, with the exhaust fan activating according to the predetermined control logic. Based on the analysis of the test results, the system achieved a 100% success rate in all scenarios tested and was able to display real-time air quality information via LCD. This study proves that the Arduino-based control system can work effectively in automatically maintaining indoor air quality and is an easy-to-implement solution.